Nitrogen mineralization and immobilization in surface sediments of coastal reclaimed aquaculture ecosystems - Lin, Xianbiao; Lin, Genmei; Zheng, Yijie; Li, Wenjing; Guo, Peng; Fan, Shiyuan; Kong, Tiantian; Tian, Dongfan; Sun, Dongyao; Shen, Zhuo (Frontiers in Marine Science, 2023)
Sediment nitrogen (N) mineralization and immobilization are two crucial processes driven by microorganisms, which may play significant roles in the regulation of water quality in aquaculture ecosystems. However, limited information is available about the quantitative importance of sedimentary N mineralization and immobilization in coastal aquaculture systems. Here, a combination of incubation experiments with a 15N isotope dilution technique were employed, aiming to quantify N mineralization and immobilization processes in surface sediments (0–5 cm) of three types of aquaculture ecosystems (seabass, white shrimp, and green crab ponds) reclaimed within the western bank of the Pearl River Estuary. Our results showed that no significant difference in sediment N mineralization and immobilization rates, microbial abundances, and organic matter among different aquaculture types on small-scale range. Meanwhile, prolonged pond-drying significant reduced sediment N mineralization and immobilization rates, bacterial abundances, organic matter, moisture content, ferrous ion (Fe2+), Fe2+/Fe3+, and ammonium (NH4+), while not strongly altered sediment percentage of NH4+ mineralized per day (PAM), relative ammonium immobilization (RAI), fungal abundances, TOC/TN, nitrate (NO3−), and δ13Corg. N mineralization and immobilization rates were both significantly related to overlying water NO3−, as well as sediment moisture content, bulk density, organic matter, Fe2+, and microbial abundances. In addition, the total mineralized and immobilized N in aquaculture surface sediments from the Guangdong-Hong Kong-Macao Greater Bay Area were estimated to be approximately 4.55×104 and 3.68×104 t N yr-1, respectively. Higher N mineralization relative to N immobilized fluxes indicated that the sediment serves as an important source of eutrophication in reclaimed aquaculture system of coastal wetlands.